Penerapan Bauran Komunikasi Pemasaran pada Wisata Religi : (Studi Kasus Wisata Religi Mlangi) - Riski Damastuti; Komang Aji Ihza Mahendra (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Based on the data obtained from the 2019 Bappeda tourism statistics, it is known that there has been a significant increase in visitors to the Mlangi Religious Tourism Village. This is quite the opposite considering that tourism which has high interest is natural and historical tourism. This study describes the efforts to implement the marketing communication mix carried out by the Mlangi Religious Tourism Village. This study uses interviews, observation, and documentation as data collection techniques. The interviewees for this research were four people who were administrators and responsible for the Mlangi Religious Tourism Village, as well as visitors to the Mlangi Religious Tourism Village. From this research it is known that the Mlangi Religious Tourism Village does not use all the elements in the marketing communication mix, but only four of the elements, namely: advertising, public relations and publicity, interactive marketing, and word of mouth marketing.